Analisis Pengendalian Persediaan Bahan Baku Insert Frame dengan Metode Economic Order Quantity pada PT SSI - Surya Kancana, Raden Mas Galih; Suseno, Agustian; Arifin, Jauhari; Maulidin, Wildan Fatchan (Fakultas Teknik Universitas Tulang Bawang, 2025)
In the manufacturing industry, optimal raw material inventory management is crucial for smooth production and cost efficiency. PT SSI faces problems in managing insert frames, which causes high ordering and storage costs. This study analyzes the application of the Economic Order Quantity (EOQ) method to determine the optimal order quantity and reduce total inventory costs. With a descriptive quantitative approach, data were collected through interviews, historical analysis of ordering and inventory costs, and calculations of EOQ and Total Inventory Cost (TIC). The results showed that the EOQ method reduced the frequency of orders from 48 to 24 times per year with an optimal order quantity of 63,155 units. Total inventory costs were also reduced from Rp 279,412,534 to Rp 230,256,690 per year, proving that the EOQ method is more efficient. The novelty of this research is the combination of EOQ with specific variables of the semiconductor industry. Further research is recommended to explore demand uncertainty and the integration of EOQ with artificial intelligence and ERP systems to improve inventory management accuracy. Keywords: Economic Order Quantity (EOQ), Inventory Control, Operational Efficiency, Optimal Order Quantity, Total Inventory Cost